Implementasi Kebijakan Kepala Madrasah dalam Penjaringan Peserta Didik Baru - Shobri, Muwafiqus; Darsiya (Journal of Education Management Research, 2023)
The student selection policy relates to the use of the basics of student management. So that someone is accepted as a student at a school, prospective students must meet the requirements as determined. Based on the research context above, the researcher's focus that will be studied in this research is how to implement the madrasah principal's policy in recruiting new students at MA Hasan Jufri. Researchers used qualitative research methods with a descriptive approach and data collection techniques used observation, interview and documentation techniques. The data analysis techniques used are data reduction, data presentation and conclusion drawing. The results of this research show that the implementation of the madrasa head's policy was carried out in collaboration with MTS Hasan Jufri by conducting outreach in the form of distributing questionnaires to find out who MTS Hasan Jufri alumni were who would continue to MA Hasan Jufri. Apart from that, it provides scholarships to new students who meet the requirements according to provisions such as tahfidz Qur'an.